THE ROLE OF NURSES IN THERAPY EDUCATION FOR NURSING STUDENTS - Hodiyeva Shaxrinoz Bobokul kizi; Orzikulova Mahliyo Okiljon kizi (Ta'lim innovatsiyasi va integratsiyasi, 2025)
Abstract The training of nurses in therapy is an essential component of modern healthcare  education.  This  article  explores  effective  methodologies  for  teaching therapy to nursing students, focusing on the role of nurses in therapeutic practice and patient care. A particular emphasis is placed on the responsibilities of nurses in therapy, including patient monitoring, medication administration, and emotional support. This study provides insights into the educational strategies that enhance learning outcomes for nursing students.